Primary hyperparathyroidism in young patients in Russia: high frequency of hyperparathyroidism-jaw tumor syndrome. Issue 8 (November 2017) - Mamedova, Elizaveta; Mokrysheva, Natalya; Vasilyev, Evgeny; Petrov, Vasily; Pigarova, Ekaterina; Kuznetsov, Sergey; Kuznetsov, Nikolay; Rozhinskaya, Liudmila; Melnichenko, Galina; Dedov, Ivan; Tiulpakov, Anatoly
Abstract : Background: Primary hyperparathyroidism (PHPT) is a relatively rare disorder among children, adolescents and young adults. Its development at an early age is suspicious for hereditary causes, though the need for routine genetic testing remains controversial. Objective: To identify and describe hereditary forms of PHPT in patients with manifestation of the disease under 40 years of age. Design: We enrolled 65 patients with PHPT diagnosed before 40 years of age. Ten of them had MEN1 mutation, and PHPT in them was the first manifestation of multiple endocrine neoplasia type 1 syndrome. Methods: The other fifty-five patients underwent next-generation sequencing (NGS) of a custom-designed panel of genes, associated with PHPT ( MEN1, CASR, CDC73, CDKN1A, CDKN1B, CDKN1C, CDKN2A, CDKN2C, CDKN2D ). In cases suspicious for gross CDC73 deletions multiplex ligation-dependent probe amplification was performed. Results: NGS revealed six pathogenic or likely pathogenic germline sequence variants: four in CDC73 c.271C>T (p.Arg91*), c.496C>T (p.Gln166*), c.685A>T (p.Arg229*) and c.787C>T (p.Arg263Cys); one in CASR c.3145G>T (p.Glu1049*) and one in MEN1 c.784-9G>A. In two patients, MLPA confirmed gross CDC73 deletions. In total, 44 sporadic and 21 hereditary PHPT cases were identified. Parathyroid carcinomas and atypical parathyroid adenomas were present in 8/65 of young patients, in whom CDC73 mutations were found in 5/8. Conclusions: Hereditary forms of PHPT can be identified in up to 1/3 of young patients with manifestation of the disease at <40 years of age. Parathyroid carcinomas or atypical parathyroid adenomas in young patients are frequently associated with CDC73 mutations.